EXPANDED LOCAL PROGRAM - Dyer, Dennis M (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Memorandum from Kurt L. Malgrem to Samuel D. Chilcote Jr. regarding expanding their local program. States that the anti tobacco groups are very adept at challenging the tobacco industry at a local level. Uses examples from California and Massachusetts to show that effective targeting of local issues can be effective. Outlines their strategy for dealing with local issues.